Stress and Diet Quality Among Ecuadorian Adults During the COVID-19 Pandemic. A Cross-Sectional Study - Abril-Ulloa, Victoria; Santos, Sueny Paloma Lima-dos; Morejón-Terán, Yadira Alejandra; Carpio-Arias, Tannia Valeria; Espinoza-Fajardo, Ana Cristina; Vinueza-Veloz, María Fernanda (Frontiers in Nutrition, 2022)
Background Stress has been associated with food habits. Stress changes eating patterns and the salience and consumption of hyperpalatable foods. During the lock-down due to the COVID-19 pandemic, stress was very common. Objective We investigated the association between stress and diet quality in Ecuadorian adults during the COVID-19 pandemic. Design A cross-sectional study. Setting Data was collected using a self-administered online survey. Stress was measured using the Perceived Stress Scale (PSS-14), and diet quality was evaluated using the Global Diet Index (GDI). A linear regression model with restrictive cubic splines was used to investigate the association between stress and diet quality. Participants Participants were recruited by convenience sampling, including a total of 2602 individuals. Most participants were female (68.57%) and had university education (78.52%), with a median age of 25 (IQR: 25, 37). Results Stress was reported by 26.06% of participants. The majority of individuals (75.79%) reported having a diet that needed changes or an unhealthy diet. Independently from biological sex, age, level of education, people/room ratio, economic allowance, and expenses for food, stress was statistically significantly associated with diet quality (p = 0.035). The association between stress and diet quality was inverse and non-linear; higher stress levels were associated with poorer diet quality. The consumption of palatable foods was not statistically significant associated with stress. Conclusions Stress is associated with poorer diet quality. Public health measures to improve the mental health and lifestyle of the population are needed during the lock-down of the pandemic.